Waste Water Management in Wet Coffee Processing Mills and their Impact on the Water quality status of Gidabo River and its Tributaries, Southern Ethiopia - Mihret Dananto Ulsido; Muhammed-Ziyad Geleto; Yohannes Seifu Berego (Environmental Health Insights, 2024)
The Gidabo River and its tributaries are the main sources of water for more than 1,584,646 inhabitants. It is an important source of water for the surrounding rural communities for various uses such as domestic, irrigation, livestock watering, fishing, and recreation. The river is the main tributary of Lake Abaya. The present study was designed to investigate the water quality status of the Gidabo River and its tributaries for domestic and aquatic life. To assess the water quality status, water samples were collected in monthly intervals for a period of 3 months from September to November (coffee processing time), 2022. Arc GIS 9.3, 3 DEM, and spreadsheet were used to analyze the data collected from SRTM (Shuttle Radar Thematic Mapper, 90 m) and field observation. Of all the water quality parameters analyzed; turbidity, BOD 5 , DO, COD, pH, Ni, Fe, NO 3 − , and PO 4 3− were higher than the recommended limits of national and international standards for aquatic life. Based on the Weighted Arithmetic Mean (WAM), Water Quality Index (WQI) calculations of the River, WQI value of the river ranges between 34.83 and 54.31 in different reaches of the watershed which is classified under bad category. The wet coffee processing industry which is the main sources of contamination in the watershed uses 63 L of processing water to produce 1 kg of green coffee beans. Traditional lagoons, with an average hydraulic retention time (HRT) of 1.99 days, are the most common methods of treating wastewater. The river is at higher risk from harmful anthropogenic activities in the watershed and requires urgent monitoring and mitigation to prevent further degradation.